Synthesis and Characterization of New Polyamino-Cholic Acid Dimers - Q. Shawakfeh, Khaled; H. Al-Said, Naim; Shawish, Ihab (Asian Journal of Chemistry, 2016)
Cholic acid was selectively protected by trifluoroacetic anhydride, then selectively deprotected at C-3 in order to synthesize 3-keto-diprotected methyl cholate. Dimerization via A-A ring connection was achieved by reductive amination of 3-keto-diprotected methyl cholate with different di and polyamines. Diamines chosen to build SAR were n = 3, 4, 6. In addition, polyamine (spermidine) was chosen to study the effect of increasing the distance between the two sides of dimer in bioactivity. Several dimeric methyl cholate derivatives were synthesized to evaluate their biological activities.